2015
DOI: 10.1039/c5ra18388j
|View full text |Cite
|
Sign up to set email alerts
|

Gel thermoresponsiveness driven by switching of the charge-transfer interaction

Abstract: A novel gel LCST system was constructed by utilizing the CT interaction between the gel and external effector, thus shrinking upon heating with hypochromic colour change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Recently, we have demonstrated LCST-type thermoresponsive polymers based on the supramolecular designs through the solvation and desolvation of the polymer chain, rather than the coil-globule transition. The addition of pseudo-solvating molecules, called effectors, to the polymer suspension in a non-solvent [59][60][61][62][63][64] induced the LCST-type phase separation under ambient conditions in non-aqueous media. At room temperature, the polymer chain was solubilized by the complex formation with the effector, similar to solvation, and at elevated temperature, the polymer chain collapsed by the dissociation of the effector from the polymer complex, similar to desolvation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have demonstrated LCST-type thermoresponsive polymers based on the supramolecular designs through the solvation and desolvation of the polymer chain, rather than the coil-globule transition. The addition of pseudo-solvating molecules, called effectors, to the polymer suspension in a non-solvent [59][60][61][62][63][64] induced the LCST-type phase separation under ambient conditions in non-aqueous media. At room temperature, the polymer chain was solubilized by the complex formation with the effector, similar to solvation, and at elevated temperature, the polymer chain collapsed by the dissociation of the effector from the polymer complex, similar to desolvation.…”
Section: Introductionmentioning
confidence: 99%
“…At room temperature, the polymer chain was solubilized by the complex formation with the effector, similar to solvation, and at elevated temperature, the polymer chain collapsed by the dissociation of the effector from the polymer complex, similar to desolvation. The two kinds of supramolecular interactions, hydrogen bonding [61][62][63][64] and charge transfer complexation, 59,60 were used to realize a desirable LCST-type phase separation. However, these designs were not accepted as the general strategy for the LCST-type phase separation because they were constructed by controlling the supramolecular interactions between specially-designed polymers and specially-designed effectors.…”
Section: Introductionmentioning
confidence: 99%
“…2,17 In addition, charge transfer complex formation between polymer and effector causing solvation can provide a posteriori acquisition of thermoresponsiveness of polymers. 16,18 These effector-induced thermoresponsive polymers occur in organic solvent systems, but they are not limited to organic solvent systems and have also been reported in aqueous systems. The combination of water-insoluble hydrophobic polymers having bulky adamantyl groups at the side chain and cyclodextrin exhibits effector-induced thermoresponsiveness in an aqueous medium through the inclusion of the adamantyl groups in the cyclodextrin.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A novel strategy for providing and regulating thermoresponsiveness to polymer species has been recently developed based on ternary systems by adding effectors to polymer and solvent systems. ,, In the ternary systems, organic molecules that can interact with polymers and regulate their solubility in the solvents are added as effectors, leading to the a posteriori acquisition of thermoresponsiveness for nonthermoresponsive polymers. As a representative, polymers with urea groups at side chains are insoluble in nonpolar organic solvents because of strong intermolecular hydrogen bonding among polymers, whereas the addition of various organic molecules with hydrogen-bonding capability provided a thermoresponsive soluble–insoluble phase transition for the polymers. , In addition, charge transfer complex formation between polymer and effector causing solvation can provide a posteriori acquisition of thermoresponsiveness of polymers. , These effector-induced thermoresponsive polymers occur in organic solvent systems, but they are not limited to organic solvent systems and have also been reported in aqueous systems. The combination of water-insoluble hydrophobic polymers having bulky adamantyl groups at the side chain and cyclodextrin exhibits effector-induced thermoresponsiveness in an aqueous medium through the inclusion of the adamantyl groups in the cyclodextrin. The supramolecular interaction between an adamantyl group and cyclodextrin weakens at increased temperature, leading to dissociation of the inclusion by cyclodextrin and precipitation of the hydrophobic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Similar LCST behavior was observed by utilization of charge transfer interaction between the pyrene group in poly((1-pyrene)methyl acrylate) and electron-accepting molecules. 38,39 Dissociation of charge transfer complexes triggers drastic change of solubility upon heating. These results clearly indicated that dissociation of supramolecular complexes between the polymer chain and the effector by heating triggers the LCST behavior.…”
mentioning
confidence: 99%